Community Satisfaction Level toward Public Services at the Population and Civil Registration Office of Central Lombok Regency in 2025: Analysis of the Community Satisfaction Index and Improvement Recommendations - Agus Agus; Ardiyansah Ardiyansah (Journal of Public Policy, Governance and Local Government, 2026)
This study aims to analyze the level of community satisfaction with public services at the Population and Civil Registration Office of Central Lombok Regency by measuring the Community Satisfaction Index (CSI) based on 14 service indicators. The study employs a quantitative approach using a survey method involving 400 respondents in 2025, with data analyzed through perception score processing. The theoretical framework is grounded in customer satisfaction theory and public service quality theory. The results indicate that the average CSI score is 3.34 with a converted value of 83.46, which falls into the “good” category (grade B). Overall, the quality of services is perceived as satisfactory. The highest scores are found in the indicators of service cost fairness and cost certainty, each achieving a perfect score of 4.00 (converted value 100.00), categorized as “very good,” reflecting high transparency and accountability in service costs. However, the lowest scores are observed in the indicators of service requirements (3.04; converted value 76.00) and service schedule certainty (2.92; converted value 73.00), both categorized as “poor.” These findings indicate that the public still faces challenges related to unclear requirements and inconsistent service schedules. Meanwhile, indicators related to staff performance and service environment are generally rated as good. This study concludes that the public service quality at the Population and Civil Registration Office of Central Lombok Regency is generally in the good category, with strong performance in cost transparency. To further improve service quality, it is recommended to simplify service requirements, enhance schedule certainty through accurate information systems, and optimize service digitalization alongside capacity building for service personnel.